Characteristic X-ray detector: In-situ imaging of radioactive contaminant distributions. (November 2015) - Kobayashi, Shingo; Shinomiya, Takayuki; Yoshida, Toru; Kitamura, Hisashi; Shirakawa, Yoshiyuki; Kurita, Kazuyoshi; Uchihori, Yukio
Abstract: The characteristic X-ray detector (CXRD), a CsI(Tl) scintillator with a 50-mm diameter, is a directional X-ray sensor that measures characteristic X-rays from radioactive material, such as 137 Cs, and identifies the direction of radioactive contamination. We evaluated a CXRD and visualized the distribution of radioactivity in the contaminated area near the Fukushima Dai-ichi nuclear power station, where the ambient dose equivalent rate was 2.1 μSv/h at 1 m above ground level. We found a good correlation between the characteristic X-ray fluxes and the distribution of radioactive contaminants with a 0.823 Pearson product–moment correlation coefficient. Highlights: We tested a characteristic X-ray detector (CXRD) to image Cs-137 distribution. The CXRD can make an image of Cs-137 contamination by detecting characteristic X-rays. The correlation between X-ray image and Cs137 contamination in-situ was tested. The CXRD has good performance to image hotspots in a contaminated area.